Gender differences in esophageal variceal bleeding in the United States. (31st December 2022) - Sohal, Aalam; Chaudhry, Hunza; Dhaliwal, Armaan; Singla, Piyush; Gupta, Gagan; Sharma, Raghav; Dukovic, Dino; Prajapati, Devang
Abstract: Background and Aims: Esophageal variceal bleeding is a common reason for hospitalization in patients with cirrhosis. The main objective of this study was to analyze the effects of gender differences on outcomes in hospitalizations related to Esophageal variceal bleeding in the United States. Methods: A retrospective observational cohort study was performed using the National Inpatient Sample (NIS) database for all hospitalizations with a discharge diagnosis of esophageal varices with hemorrhage from 2016 to 2019. The primary outcome was in-hospital mortality, while secondary outcomes included rate of early endoscopy (defined as less than 1 day), AKI, blood transfusion, sepsis, ICU admission and TIPS (Transjugular Intrahepatic Portosystemic Shunt). We also compared the length of stay and total hospitalization charges. Results: We identified a total of 166, 760 patients with variceal bleeding of which 32.7% were females. In-hospital mortality was higher in males, 9.91%, compared to females, 8.31% (adjusted odds ratio (aOR): 0.88, p-value=.008, when adjusted for confounding factors). The odds of undergoing an EGD, length of stay, or total hospitalization charges did not differ between the two groups. Compared to men, women had lower odds of receiving TIPS (aOR = 0.83, p-value=.002). Conclusion: Women hospitalised with esophageal variceal bleeding are at a lower risk of death compared to males. Further research is needed to elucidate the factors associated with this lower risk.